Stress on the streets: Validation of a measurement. Issue 1 (2nd January 2016) - Rew, Lynn; Powell, Tara; Thompson, Sanna
Abstract: Background: Homeless and street-dependent youths experience myriad stressors, but to date there has been no published measure of this phenomenon. Objective: This study was designed to describe the process of developing and testing a measure of stress experienced on the streets suitable for use with this population. Methods: Classical measurement theory was used to develop and evaluate relevance and validity of items in the scale. Results: The total scale content validity index was .95 and the Cronbach's alpha was .92 in a combined sample of homeless youths ( n  = 90) and university students ( n  = 94). The mean scores of the two subsamples were statistically significantly different (t(166) = 4.22, P  < .001), supporting construct validity. Factor analysis, using Principal Component Analysis, of data collected from the homeless youths yielded five subscales congruent with content in initial item construction. The subscales were: (1) safety on the streets, (2) housing stability, (3) interpersonal relationships, (4) immediate security and (5) stress about future. Conclusions: The final scale has 27 items suitable for future research with this population.